Does Training Innate Immunity Confer Broad-spectrum Protection Against Bone and Joint Infection in a Mouse Model?. Issue 11 (November 2020) - Zhu, Hongyi; Lin, Junqing; Wei, Haifeng; Bao, Bingbo; Gao, Tao; Zheng, Xianyou
Abstract: Background: The innate immune system can recall previous immunologic challenges and thus respond more effectively to subsequent unrelated challenges, a phenomenon called trained immunity. Training the innate immune system before surgery might be a potential option to prevent bone and joint infection. Questions/purposes: (1) Does the training process cause adverse effects such as fever or organ injury? (2) Does training the innate immune system confer broad-spectrum protection against bone and joint infection in a mouse model? (3) Does trained immunity remain effective for up to 8 weeks in this mouse model? Methods: After randomization and group information blinding, we trained the innate immune system of C57BL/6 mice (n = 20 for each group) by intravenously injecting them with either 0.1 mg of zymosan (a toll-like receptor 2 agonist), 0.1 mg of lipopolysaccharide (a toll-like receptor 4 agonist), or normal saline (control). For assessing the host response and possible organ injury after training and infection challenge, we monitored rectal temperature, collected blood to determine leukocyte counts, and performed biochemical and proinflammatory cytokine analyses. After 2 weeks, we then assessed whether trained immunity could prevent infections in an intraarticular implant model subjected to a local or systemic challenge with a broad spectrum of bacterial species ( Staphylococcus aureus, Escherichia coli, Enterococcus faecalis, Streptococcus pyogenes, or Pseudomonas aeruginosa ) in terms of culture-positive rate and colony counts. The proportion of culture-positive joint samples from trained and control groups were compared after 4 weeks. Finally, we increased the interval between training and bacterial challenge up to 8 weeks to assess the durability of training efficacies. Results: Training with zymosan and lipopolysaccharide caused mild and transient stress in host animals in terms of elevated rectal temperature and higher blood urea nitrogen, creatinine, alanine aminotransferase, and aspartate aminotransferase levels. Trained mice had fewer culture-positive joint samples after local inoculation with S. aureus (control: 100% [20 of 20]; zymosan: 55% [11 of 20], relative risk 0.55 [95% CI 0.37 to 0.82]; p = 0.001; lipopolysaccharide: 60% [12 of 20], RR 0.60 [95% CI 0.42 to 0.86]; p = 0.003) and systemic challenge with S. aureus (control: 70% [14 of 20]; zymosan: 15% [3 of 20], RR 0.21 [95% CI 0.07 to 0.63]; p = 0.001; lipopolysaccharide: 15% [3 of 20], RR 0.21 [95% CI 0.07 to 0.63]; p = 0.001) than controls. We observed similar patterns of enhanced protection against local and systemic challenge of E. coli, E. faecalis, S. pyogenes, and P. aeruginosa . Zymosan-trained mice were more effectively protected against both local (control: 20 of 20 [100%], zymosan: 14 of 20 [70%], RR 0.70 [95% CI 0.53 to 0.93]; p = 0.02) and systemic (control: 70% [14 of 20]; zymosan: 30% [6 of 20], RR 0.43 [95% CI 0.21 to 0.89]; p = 0.03) challenge with S. aureus for up to 8 weeks than controls. Conclusions: Trained immunity confers mild stress and broad-spectrum protection against bone and joint infection in a mouse model. The protection conferred by immunity training lasted up to 8 weeks in this mouse model. The results of the current research support further study of this presurgical strategy to mitigate bone and joint infection in other large animal models. Clinical Relevance: If large animal models substantiate the efficacy and safety of presurgical immunity training-based strategies, clinical trials would be then warranted to translate this strategy into clinical practice.